Keberpihakan Gereja terhadap Kaum Miskin dalam Terang Evangelii Gaudium - Akrimianus Suhardi; Felix Riondi Sugar; Yoseph Taus; Marselinus Langgor; Protasius Karsa; Falentinus Carles; Yohanes Reinaldi Lagang; Adrianus Loe (Atmosfer: Jurnal Pendidikan, Bahasa, Sastra, Seni, Budaya, dan Sosial Humaniora, 2026)
Widespread structural poverty is one of the tangible effects of a capitalist economic system that emphasizes capital accumulation and economic growth without regard for equity and social justice. This situation has prompted the Church to reexamine its role in a world marked by inequality and marginalization of the poor. This article aims to analyze the relevance of Pope Francis' thinking in the apostolic exhortation Evangelii Gaudium as a theological and pastoral basis for the Church's stance towards the poor. This study uses a qualitative method with a literature review approach through document study, with Evangelii Gaudium as the main source, supported by relevant social theology literature and academic studies. The results of the study show that Pope Francis comprehensively understands poverty in three dimensions, namely material, moral, and spiritual poverty. Through Evangelii Gaudium, the Church is called to experience a change in its mission, from a self-centered Church to a Church that moves outward and is actively involved in the liberation of the poor. Thus, the Church not only carries out charitable works, but also acts as an agent of social change that brings the joy of the Gospel, justice, and hope to a world wounded by structural injustice.